Mosque Accounting Management as a Solution to Transparency and Public Accountability at the Al-Barokah Mosque, Tegal Regency - Safitri, Dian; Putri, Nurul Wulandari (MultiTech Publisher, 2024)
A mosque is a facility whose location and role are very strategic in Islam. Mosques can not only be used as places of worship but also for other social activities. However, in reality, places of worship are only used as places for the implementation or practice of ritual worship such as prayers, prayers and dikir. Mosques play an important role and therefore mosques are as strategic as other public sector organizations. It is also important to pay attention to accountability and transparency in managing mosque finances. Mosque managers must fulfill their responsibilities, carry out financial management well, and record and report the mosque's financial management clearly. There is also a need for transparency in financial transactions in managing mosque finances. The funds managed by the mosque are entrusted by the people for the common benefit, so the financial management of the mosque must be carried out with full responsibility and transparency